Analisis QoS (Quality of Service) Perangkat IoT pada Pendingin Ruangan Server PT.Skynet Indonesia Madani - supardianto, supardianto; Mansyur, Agus Maulidi; Fani, Maidel (Software Development, Digital Business Intelligence, and Computer Engineering, 2023)
PT Skynet Indonesia Madani, a telecommunications company based in Batam City, specializes in providing Broadband Internet and Dedicated Internet services as an Internet Service Provider (ISP). With servers capable of supporting up to 5,000 customers across various areas in Batam City, maintaining network stability is paramount. A critical component of this stability is the server room's temperature regulation. Regular monitoring and control of the air conditioning in the server room are essential to prevent device failures due to errors or overheating. To enhance reliability and reduce human error, an automatic control system for the server room's air conditioning was developed. This system, built using Wemos D1 R1, DHT11 Module, IR Transceiver, PZEM V2.0, Tp-link TL-WR840N, and Tp-link TL-SF1008D, offers features such as scheduled cooling activation, real-time server room temperature monitoring, and notification capabilities for air conditioning disruptions. The system is web-based, facilitating remote access and control. The development approach for this system employed the Waterfall method, complemented by QoS (Quality of Service) analysis techniques. This research aims to evaluate the quality and effectiveness of the automatic control system for PT Skynet Indonesia Madani's server room air conditioning.